A high strength and high electrical conductivity bulk Cu-Ag alloy strengthened with nanotwins. (1st March 2017) - Zhang, B.B.; Tao, N.R.; Lu, K.
Abstract: A bulk solid solution Cu-5Ag alloy consisting of nanotwins and nanograins was prepared by means of dynamic plastic deformation at liquid nitrogen temperature. Continuous precipitation of Ag occurs in the nanotwins which exhibit higher thermal stability than the nano-grains upon annealing. A tensile strength of 870 MPa and an electrical conductivity of 78% International Annealed Copper Standard are achieved in the annealed nanostructure Cu-5Ag alloy which is strengthened with nanotwins and nanoscale precipitates. Graphical abstract: